(untitled) (Gumilyov Journal of Pedagogy, 2026)
The current socioeconomic and cultural conditions of society’s development make the education of today’s youth one of the most pressing issues. Globalization, the expansion of the information space, and the transformation of value systems directly influence the worldview and behavior of young people. In this regard, our article examines the importance of nurturing modern youth based on spiritual and moral values. In the context of globalization, the system of spiritual and moral values in society is constantly undergoing change, and factors such as the development of science and technology, the abundance of digital information, and cultural diversity are exerting new influences on the spiritual world of today’s youth, influencing the formation and development of consciousness in both positive and negative ways. In this situation, preserving spiritual and moral values and instilling correct life guidelines in today’s youth is one of the most important tasks of modern society. Spiritual and moral values lay the foundation for the personal development of today’s youth, their life attitudes, and their social adaptation. After analyzing the works of international and Kazakh scholars, we concluded that not only the family but also the social environment, the educational process at higher education institutions, and the influence of social circles and friends play a significant role in nurturing today’s youth based on spiritual and moral values. During the study, a survey was conducted among today’s youth, and a quantitative and qualitative analysis of the data was conducted. The results confirm the importance of supporting and developing spiritual and moral values in the education of today’s youth.